Sensitivity of Sediment Magnetic Records to Climate Change during Holocene for the Northern South China Sea - Ouyang, Tingping; Li, Mingkun; Zhao, Xiang; Zhu, Zhaoyu; Tian, Chengjing; Qiu, Yan; Peng, Xuechao; Hu, Qiao (Frontiers in Earth Science, 2016)
Magnetic property has been proved to be a sensitive proxy to climate change for both terrestrial and marine sediments. Based on the schedule frame established by AMS 14C dating of foraminifera, detail magnetic analyses were performed for core PC24 sediments at sampling intervals of 2 cm to discuss magnetic sensitivity of marine sediment to climate during Holocene for the northern South China Sea. The results indicated that: 1) Concentration dependent magnetic parameters are positive corresponding to variation of temperature. The frequency dependent susceptibility coefficient basically reflected the variation in humidity; 2) XARM/SIRM was more sensitive to detrital magnetite particles and SIRM/X was more effective to biogenic magnetite particles. Variations of XARM/SIRM and SIRM/X are corresponding to precipitation and temperature, respectively; 3) the Holocene Megathermal in the study area was identified as 7.5-3.4 cal. ka BP. The warmest stage of Holocene for the study area should be during 6.1 to 3.9 cal. ka BP; 4) The 8 ka cold event was characterized as cold and dry during 8.55 to 8.25 cal. ka BP; 5) During early and middle Holocene, the climate combinations were warm dry and cold wet. It turned to warm and wet after 2.7 cal. ka BP.